Rebuilding Coastal Institutions for Sustainable Fisheries Value Chains: Challenges and Pathways from Bajoe, Indonesia - Jumiati, Jumiati; Indrawati, R A; Megawati, Megawati; MR, Syarifa Aeni; Ismail, Ismail (Jurnal Sosial Ekonomi Kelautan dan Perikanan, 2025)
Local institutions play a pivotal role in enhancing the sustainability of small-scale capture fisheries value chains, yet their contributions often remain fragmented and underexplored. This study analyzes the roles, challenges, and opportunities of local institutions—including fishermen’s groups, cooperatives, and village-owned enterprises—in supporting each stage of the fisheries value chain in Bajoe Village, Bone Regency, South Sulawesi. Using a qualitative exploratory case study, data were collected through in-depth interviews, participatory observation, focus group discussions, and document analysis. The findings reveal that government assistance programs have reached fishing communities but are unevenly distributed and highly dependent on active groups or elite networks. Institutional capacity remains weak, with cooperatives largely inactive and fishermen heavily reliant on mediators under informal patron–client arrangements. However, emerging aspirations for cooperative revitalization, digital marketing, and product diversification demonstrate strong potential for institutional renewal. This study introduces an integrative analytical model linking community-based institutional dynamics with value-chain governance—an approach rarely applied in Indonesian small-scale fisheries. Policy recommendations highlight the need for participatory governance reforms, equitable access to infrastructure and finance, and integration of digital innovations to strengthen fishermen’s bargaining position and ensure a more inclusive, resilient, and sustainable coastal econom.